IMF Staff papers : Volume 20 No. 1. (IMF Staff Papers; IMF Staff Papers ;, 1973)
This paper focuses on theoretical and policy issues posed by financial integration among industrial countries since the mid-1950s. The problems of measuring international financial integration and of estimating its trend over the years are also explored. The role of the Euro-dollar market, as a major financial intermediary that channels short-term funds between the money markets of the industrial countries, is examined first. An econometric analysis of factors influencing the Euro-dollar interest rate indicates that its movements are dominated by conditions in the United States and suggests a high degree of integration between the US and Euro-dollar capital markets. However, the results also lend some support to the view that the Euro-dollar rate is influenced by conditions in Europe, particularly by bursts of speculation. Since neither sterilization policies nor intervention in capital movements is likely to be entirely successful, highly integrated economies might also tend to determine their interest rates partly in the light of interest rate developments overseas.